Optimization for the production of ammonia from urea in a semi-batch reactor for safe feedstock in power plants: Experimental and statistical studies - Sahu, J.N.; Meikap, B.C.; Patwardhan, A.V. (Wiley-Blackwell, 2010)
Urea hydrolysis for production of ammonia, in different application areas require safe use of ammonia, for removal of the NO(x) contaminates contained in a flue gas stream and increase in the efficiency of an electrostatic precipitator for the removal of fly ash from the flue gas stream. The single and combined effects of operating parameters such as initial feed concentrations, temperatures, reaction times, and stirring speeds on the production of ammonia from urea were analyzed using response surface methodology (RSM). Analysis of variance (ANOVA) showed a high coefficient of determination value (R(2) = 0.967) and satisfactory prediction second order regression model was derived. The optimum production conditions determined for semi-batch reactor were temperature 178 degrees C, initial feed concentration 22.24 wt% of urea, time of reaction 43.2 min and stirring speed 1045 rpm. At optimum conversion conditions, the conversion of urea for production of ammonia was found to be >= 13%.